Anxiety During Employment-Seeking for Autistic Adults - Tamara Hildebrandt; Kate Simpson; Dawn Adams (Brain Sciences)
Background/Objectives: Autistic adults are more likely to be unemployed compared to neurotypical adults and those with disability. To address these poorer employment outcomes, it is important to consider factors that may be impacting on autistic adults’ employment outcomes. Anxiety is a common co-occurring condition for autistic adults; however, there is little research on how anxiety affects or influences autistic people’s experience across the employment-seeking process. The aim of this study was to explore whether anxiety is perceived to affect autistic adults’ ability to engage in employment-seeking tasks. Methods: Online, semi-structured interviews were conducted with 12 autistic adults (22–52 years) who were actively seeking employment or had sought employment in the last 18 months. Interview transcripts were analysed using thematic analysis. Results: Three themes were generated from the data analysis. Theme 1, Finding the “sweet spot”, identified some level of anxiety—but not too much—was helpful in performing the employment-seeking tasks and this “spot” could vary depending on the person and the task. Theme 2, Anxiety affects the ability to perform and function, encapsulates the autistic person’s experience when anxiety is too high. The third theme, The “vicious cycle” of anxiety and employment-seeking behaviours, explores participants’ ongoing experience of anxiety on their employment-seeking behaviours. Conclusions: The findings suggest that autistic job candidates would benefit from tailored accommodations and adjustments offered throughout the recruitment process, to reduce anxiety and improve employment-seeking outcomes for autistic candidates.